SELECTED PLASMA CONSTITUENTS OF BROILER CHICKENS FED DIFFERENT LEVELS OF DRIED SWEET ORANGE (CITRUS SINENSIS)PEELS - A. Ebrahimi; A. A. A. Qotbi A. Seidavi; F. W. Edens; V. Laudadio; V. Tufarelli (Journal of Animal and Plant Sciences, 2016)
An experiment was conducted to evaluate the effects of different levels of dried Citrus sinensis peel (DCSP) on selected plasma constituents of broilers. Data from five dietary treatments with four replicates per treatment were analyzed using a completely randomized design. Dietary treatments comprised: (1) control consisting of standard basal-diet without DCSP, (2) DCSP-1, basal starter diet supplemented with 1.5% DCSP from 1-21 days of age followed by standard basal grower diet with no DCSP from 22- 42 days of age, (3) DCSP-2, standard diets supplemented with 1.5% DCSP from 1-42 days of age, (4) DCSP-3, basal starter diet supplemented with 3.0% DCSP from 1-21 days of age followed by standard basal grower diet with no DCSP from 22- 42 days of age, and (5) DCSP-4, standard (basal starter followed by basal grower) diets supplemented with 3.0% DCSP from 1-42 days of age. Plasma constituents (glucose [GLU], cholesterol [CHOL], low density lipoprotein [LDL], high density lipoprotein [HDL], triglycerides [TGL], alkaline phosphatase activity [ALP] and uric acid [UA]) were measured at 42 days of age. DCSP decreased plasma CHOL, LDL, and TGL, but HDL was not affected significantly. Plasma GLU was decreased significantly at 42 days by 3.0% DCSP feeding 1-21 days. Plasma GLU was decreased similarly by continuous feeding of 1.5% and 3.0% DCSP from 1-42 days. Plasma ALP activity and UA concentrations were not altered significantly by DCSP feeding. Thus, using DCSP as an alternative feedstuff for broilers did not have overt negative effects on selected plasma constituents.
Keywords: Citrus sinensis; Dried peel; Broiler; Plasma traits